“Return of Mental Borders”: A Diary of COVID-19 Closures between Kehl, Germany, and Strasbourg, France - Wassenberg, Birte (Borders in Globalization Review, 2020)
This paper retraces the author’s personal experience of the COVID-19 lockdown from March to July 2020 at the Franco-German border from a threefold perspective: that of a cross-border worker living in Kehl, Germany, and working in Strasbourg, France; that of a Franco-German citizen with a family and children of both French and German nationality; and that of a researcher specialized in border studies. The paper deals with national re-bordering policies and their direct personal and psychological consequences for borderlanders, and also questions whether such measures are adequate to contain the pandemic, especially in a context of European Union integration which is based on the principle of a “Europe without borders”.